Online Learning amid COVID-19 Pandemic: Providing Assessment that Ensures Meaningful Learning Experience - Abdul Halim; Noor Eka Chandra; Rina Listia; Rizky Amelia; Yih-Sheue Lin (English Department FBS UNP, 2022)
The paper aims to explore how assessment with principles can be utilized by a teacher during online learning in pandemic situation. Since at the end of year 2019, SARS-CoV-2 virus, also well-known as COVID-19, has affected the global activities including education. Many governments decided to shift the education process from traditional face-to-face classroom to online learning either in synchronous or asynchronous modes. By utilizing systematic review as a method of study, the databases from ERIC, Google Scholar, and DOAJ were used to collect some articles that were related to the studies. These articles were selected through the process of identifying, screening, checking for eligibility, and deciding for inclusion. The findings indicated there are some modes of assessment that not only is it plausible, the varied kinds of assessment would also be a solution for the current real-life educational problems faced by the teachers.